Implementation and Challenges of the Personal Data Protection Law in Indonesia - Fachrul Razi; Hadi tuasikal; Dwi Pratiwi Markus (Publikasi Indonesia, 2024)
Law No. 27 of 2022 concerning Personal Data Protection (PDP Law) is an important milestone in Indonesia's efforts to protect the privacy and personal data of its citizens. This paper analyzes the background of the passage of the law, the main content of the regulation, implementation challenges, data leakage case studies, comparisons with international regulations, and recommendations for improving personal data protection in Indonesia.